Sosialisasi Strategi Variasi Mengajar yang Menyenangkan bagi Pendidik di SMK Karya Muda Kota Depok - Rahmadi, Darmawan; Barkah, Januar; Suaedah, Siti; Nuwayyar, Rizka (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
As times evolve, particularly in the field of education, the learning process has undergone significant changes. Therefore, educators are required to provide engaging and varied teaching methods. It has been observed at one school in Depok, SMK Karya Muda, that there is a lack of teaching variation, such as the use of different learning resources, teaching tools, and instructional media. This has led to students feeling bored and disengaged. As a result, students experience a decline in enthusiasm, interest, and motivation to learn, which negatively affects their academic performance in several subjects. To address this issue, a proposed solution is to conduct a socialization program for educators at SMK Karya Muda, Depok, on how to implement engaging and varied teaching methods. This includes diversifying learning resources, teaching tools, instructional media, and teaching methods to enhance students' enthusiasm, interest, and motivation, ultimately improving their academic performance at SMK Karya Muda.